Taguchi Design of Experiment (DoE) for Evaluating TIG-welding Parameter Variations on Tensile-shear Load and Hardness Using Stainless Steel 304 Material - Siswanto; Sukarman; Dodi Muyladi; Amir; Amri Abdulah; Ean Deka Putra (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
This article delves into the intricacies of optimizing the TIG welding process using stainless steel 304 (SUS 304) material, with particular emphasis on small-scale industries that are heavily reliant on TIG welding, especially in the production of household equipment and fences. The objective of this research is to enhance the tensile shear load (T's load) through the Taguchi Design of Experiment (DoE), which takes into account welding current, gas flow rate, and electrode diameter as primary parameters. This study evaluates T's load and hardness across the welding zone, which includes the heat-affected zone (HAZ) and base metal. The study was conducted using a Stahlweld inverter welding machine operating at 220 V/50 Hz, and a maximum T's load of 1545.1 kgf was achieved in the fourth iteration. The optimization of T's load was carried out using SN ratio analysis and involved setting the welding current to level II, gas flow rate to level I, and electrode diameter to level II following the Taguchi DoE design. The hardness peaks in the weld area decreased in the HAZ and reached their lowest point in the base metal. These findings provide valuable insights into optimizing TIG welding parameters for thin stainless steel 304 materials, which supports Sustainable Development Goal 9 (industry, innovation, and infrastructure).